2005
DOI: 10.2134/jeq2002.0529
|View full text |Cite
|
Sign up to set email alerts
|

Planned versus Actual Outcomes As a Result of Animal Feeding Operation Decisions for Managing Phosphorus

Abstract: The paper explores how decisions made on animal feeding operations (AFOs) influence the management of manure and phosphorus. Variability among these decisions from operation to operation and from field to field can influence the validity of nutrient loss risk assessments. These assessments are based on assumptions that the decision outcomes regarding manure distribution will occur as they are planned. The discrepancy between planned versus actual outcomes in phosphorus management was explored on nine AFOs mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…The differences were mainly a result of better knowledge about the nutrient status of the fields obtained by creation of the first individual field records containing detailed information about the fields including: soil type, slope, nearness to water bodies, previous fertilizer and manure applications, the soil test status of the fields, etc. Whether farmers implement the recommendations is a matter of choice that can be affected by many factors (Beegle et al, 2000; Cabot and Nowak, 2005) and can be analyzed using econometric techniques. Probit models for panel data were used to calculate the probability of excess application of manure P compared with recommended amounts of manure P in the NMP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences were mainly a result of better knowledge about the nutrient status of the fields obtained by creation of the first individual field records containing detailed information about the fields including: soil type, slope, nearness to water bodies, previous fertilizer and manure applications, the soil test status of the fields, etc. Whether farmers implement the recommendations is a matter of choice that can be affected by many factors (Beegle et al, 2000; Cabot and Nowak, 2005) and can be analyzed using econometric techniques. Probit models for panel data were used to calculate the probability of excess application of manure P compared with recommended amounts of manure P in the NMP.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that implementing NMPs requires farmers to change their management of the farm at the strategic, tactical, and operational levels (Beegle et al, 2000; Cabot and Nowak, 2005; Tao et al, 2010). The factors that contribute to the likelihood of implementation by farmers include: (i) farm characteristics such as farm size and farm type (Halstead et al, 1990; Paudel et al, 2008); (ii) farmer characteristics such as age, education, attitude toward environmental concerns, contact with extension, and attitude toward new programs (Horan and Ribaudo, 1999; Nkamleu and Adesina, 2000); (iii) farm business characteristics and socioeconomic factors such as tenure and farm income, credit, and debt (Kim et al, 2005; Nkamleu and Adesina, 2000; Rahelizatovo and Gillespie, 2004; Smit and Smithers, 1992); and (iv) applicability of the NMPs to a given farm (Bosch et al, 1995; Diep and Beaulieu, 2005; Fuglie and Kascak, 2001; Hidsley, 2002; Paudel et al, 2008).…”
mentioning
confidence: 99%
“…Nine of the 10 commercial farms in the watershed study area allowed researchers on their fields to obtain soil samples based on a 1-ha sampling grid (Cabot and Nowak 2005). In total, 3410 environmental soil samples (i.e., 5-cm samples using Bray 1 protocols) were taken across the 217 fields (1267 ha) managed by these farms in the watershed.…”
Section: Fine-scale Disproportionalitymentioning
confidence: 99%
“…Application of recommended amounts of nutrients from manure is difficult for farmers. Numerous tactical and operational factors, such as weather, machinery constraints, and the cultural preferences of farmers can substantially change the amount of nutrients applied from the amount recommended in the NMP (Cabot and Nowak, 2005). In the absence of penalties, farmers tend to distribute manure to the nearby fields at rates that provide excess nutrients, mainly N and P, to crops (Innes, 2000).…”
mentioning
confidence: 99%